Modeling COVID-19 dynamics in the Basque Country: characterizing population immunity profile from 2020 to 2022 - Bechir Naffeti; Zeineb Ounissi; Akhil Kumar Srivastav; Nico Stollenwerk; Joseba Bidaurrazaga Van-Dierdonck; Maíra Aguiar (BMC Infectious Diseases)
Abstract Background COVID-19, caused by SARS-CoV-2, has spread globally, presenting a significant public health challenge. Vaccination has played a critical role in reducing severe disease and deaths. However, the waning of immunity after vaccination and the emergence of immune-escape variants require the continuation of vaccination efforts, including booster doses, to maintain population immunity. This study models the dynamics of COVID-19 in the Basque Country, Spain, aiming to characterize the population’s immunity profile and assess its impact on the severity of outbreaks from 2020 to 2022. Methods A SIR/DS model was developed to analyze the interplay of virus-specific and vaccine-induced immunity. The model includes three levels of immunity, with boosting effects from reinfection and/or vaccination. It was validated using empirical daily case data from the Basque Country. The model tracks shifts in immunity status and their effects on disease dynamics over time. Results The COVID-19 epidemic in the Basque Country progressed through three distinct phases, each shaped by dynamic interactions between virus transmission, public health interventions, and vaccination efforts. The initial phase was marked by a rapid surge in cases, followed by a decline due to strict public health measures, with a seroprevalence of $$1.3%$$ 1.3 % . In the intermediate phase, multiple smaller outbreaks emerged as restrictions were relaxed and new variants, such as Alpha and Delta, appeared. During this period, reinfection rates reached $$20%$$ 20 % , and seroprevalence increased to $$32%$$ 32 % . The final phase, dominated by the Omicron variant, saw a significant rise in cases driven by waning immunity and the variant’s high transmissibility. Notably, $$34%$$ 34 % of infections during this phase occurred in the naive population, with seroprevalence peaking at $$43%$$ 43 % . Across all phases, the infection of naive and unvaccinated individuals contributed significantly to the severity of outbreaks, emphasizing the critical role of vaccination in mitigating disease impact. Conclusion The findings underscore the importance of continuous monitoring and adaptive public health strategies to mitigate the evolving epidemiological and immunological landscape of COVID-19. Dynamic interactions between immunity levels, reinfections, and vaccinations are critical in shaping outbreak severity and guiding evidence-based interventions.